Applicant perceptions of selection methods for health professions education: Rationales and subgroup differences. Issue 2 (23rd October 2022) - Fikrat‐Wevers, Suzanne; Stegers‐Jager, Karen; Groenier, Marleen; Koster, Andries; Ravesloot, Jan Hindrik; Van Gestel, Renske; Wouters, Anouk; van den Broek, Walter; Woltman, Andrea
Abstract: Context: Applicant perceptions of selection methods can affect motivation, performance and withdrawal and may therefore be of relevance in the context of widening access. However, it is unknown how applicant subgroups perceive different selection methods. Objectives: Using organisational justice theory, the present multi‐site study examined applicant perceptions of various selection methods, rationales behind perceptions and subgroup differences. Methods: Applicants to five Dutch undergraduate health professions programmes ( N  = 704) completed an online survey including demographics and a questionnaire on applicant perceptions applied to 11 commonly used selection methods. Applicants rated general favourability and justice dimensions (7‐point Likert scale) and could add comments for each method. Results: Descriptive statistics revealed a preference for selection methods on which applicants feel more 'in control': General favourability ratings were highest for curriculum‐sampling tests (mean [ M ] = 5.32) and skills tests ( M  = 5.13), while weighted lottery ( M  = 3.05) and unweighted lottery ( M  = 2.97) were perceived least favourable. Additionally, applicants preferred to distinguish themselves on methods that assess attributes beyond cognitive abilities. Qualitative content analysis of comments revealed several conflicting preferences, including a desire for multiple selection methods versus concerns of experiencing too much stress. Results from a linear mixed model of general favourability indicated some small subgroup differences in perceptions (based on gender, migration background, prior education and parental education), but practical meaning of these differences was negligible. Nevertheless, concerns were expressed that certain selection methods can hinder equitable admission due to inequal access to resources. Conclusions: Our findings illustrate that applicants desire to demonstrate a variety of attributes on a combination of selection tools, but also observe that this can result in multiple drawbacks. The present study can help programmes in deciding which selection methods to include, which more negatively perceived methods should be better justified to applicants, and how to adapt methods to meet applicants' needs. Abstract : The authors report that applicants to undergraduate health professions education prefer selection methods that provide a sense of control and allow the demonstration of more than just academic ability.